2016
DOI: 10.13189/ujer.2016.040523
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Internal Marketing on Organizational Citizenship Behavior of Academic Staff in Higher Educational Institutions

Abstract: Due to their important roles in organizational performance, internal marketing and organizational citizenship behavior have become more interesting subjects among researchers and practitioners. However, empirical research is limited in the literature, and the relationship between these two variables in higher educational institutions is not clear. Hence, the purpose of this study was to examine the effect of internal marketing on organizational citizenship behavior of academic staff in higher educational insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
(16 reference statements)
1
6
0
Order By: Relevance
“…In most of the empirical studies conducted in various service sectors, it was seen that there was a positive and significant relationship between internal marketing and OCB (Alper Ay, 2018;Alshurideh, Alhadid and Barween, 2015;Chang, Tseng and Chen, 2012;Seyed Javadin, Rayej, Yazdani, Estiri and Aghamiri, 2012;Yildiz, 2016b). Our study on employees in the sports industry has shown that, similar to other research, internal marketing affects OCB significantly and positively.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In most of the empirical studies conducted in various service sectors, it was seen that there was a positive and significant relationship between internal marketing and OCB (Alper Ay, 2018;Alshurideh, Alhadid and Barween, 2015;Chang, Tseng and Chen, 2012;Seyed Javadin, Rayej, Yazdani, Estiri and Aghamiri, 2012;Yildiz, 2016b). Our study on employees in the sports industry has shown that, similar to other research, internal marketing affects OCB significantly and positively.…”
Section: Discussionsupporting
confidence: 83%
“…On the other hand, civic virtue is defined as behaviors that indicate employees' participation in the political life of the organization, their commitment, and interest at the macro-level (Podsakoff, MacKenzie, Paine and Bachrach, 2000). In the literature, there are studies examining the impact of internal marketing on issues such as organizational commitment (Candan and Gündüz Çekmecelioğlu, 2009;Dokuzoğlu and Eren, 2020;Kocaman, Durna and İnal, 2013;Taşkın and Yeni, 2016;Tuncay, 2018;Yeniçeri, Kurt and Akgül, 2020;Yıldız, 2020), job satisfaction (Arslanoğlu, Bektemür and Gemlik, 2020;Baran and Arabelen, 2017;Eşitti and Buluk, 2018;Öngel and Şenol, 2019;Özçifçi, 2018;Yıldız, 2011), job performance (Duyan, 2020;Eşitti and Buluk, 2018), and OCB (Abzari and Ghujali, 2011;Eren, Kaygisiz and Katlav, 2016;Mülayim, 2013;Yildiz, 2016b). While the studies in the literature generally include studies aimed at determining the relations of internal marketing with different variables, it is seen that studies on OCB are not very common.…”
Section: Introductionmentioning
confidence: 99%
“…Human resources in these institutions have an important role in reaching the best educational service. In this context, academic staff are perceived as one of the most crucial elements in human resources that influence the performance of a higher educational institution and determine its quality (Yildiz, 2016). Teaching, research, and scholarly activities are among the primary tasks of academic staff.…”
Section: Introductionmentioning
confidence: 99%
“…On the similar line, Ali ( 2016) also emphasised the relationship between internal marketing, organizational commitment and job satisfaction among employees. Yildiz (2016) through two successive empirical studies confirmed that internal marketing, organizational citizenship behaviour and commitment have significant affirmative association among them. The study also revealed that internal marketing act as an effectual device for the developing organisation citizenship behaviour and work engagement among faculty members.…”
Section: Role Of Internal Marketing In Determiningmentioning
confidence: 83%